2016
DOI: 10.21608/ajas.2016.2071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Proximate Chemical Composition and Nutritional Status of Wheat Biscuits Fortified with Oat Powder

Abstract: Oat (Avena sp.) is a species of cereal grain grown for its seeds and it contains many valuable constituents. Gross chemical composition, caloric value, minerals, vitamins and amino acids composition of two oat varieties namely: Common oat (Avena sativa), and Red oat (Avena byzantina),were assessed. Data revealed that, common and red oat had a high content of total carbohydrates (75.625 and 69.435%) and protein (11.61 and 13.62%). Oat powder is rich source of P, K and Mg (472.57-469.61mg), (350-362mg) and (120.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Data as regard to biscuits formulae showed that addition of oat and whey cheese improved all of the sensory attributes scores without significant (p≥0.05) different as compared to the control formula. These findings are supported by the observation of Youssef et al, (2016), who reported that highly acceptable biscuits formula could be obtained by incorporating 10%…”
supporting
confidence: 81%
“…Data as regard to biscuits formulae showed that addition of oat and whey cheese improved all of the sensory attributes scores without significant (p≥0.05) different as compared to the control formula. These findings are supported by the observation of Youssef et al, (2016), who reported that highly acceptable biscuits formula could be obtained by incorporating 10%…”
supporting
confidence: 81%
“…Oat grains contain signifcant amounts (mg/100 g) of vitamins such as thiamine Te Scientifc World Journal (0.76), ribofavin (0.14), niacin (0.96), pantothenic acid (1.35), vitamin B-6 (0.12), and total folate (56) [29]. On the other hand, Youssef et al [39] reported in mg/100 g of oats' vitamin C (0.1), thiamine (0.44-0.53), ribofavin (0.40-0.60), and vitamin E (0.13-0.87), while Gabrovska et al [77] also reported vitamin C (0.1), niacin (0.68), vitamin B-6 (0.18), and vitamin E (1.32).…”
Section: Micronutrients Of Oatsmentioning
confidence: 99%
“…Barbara et al (2020) indicated that oat flour contained 12.37% moisture, 13.27% protein, 1.83% ash, and 12.9% dietary fiber. Meanwhile, Youssef et al (2016) revealed that the chemical composition of oat flours ranged between 9.96 -10.47% moisture, 11.61 -13.62% crude protein, 7.23 -8.92% crude fat, 3.535 -5.875%, crude fiber, 2 -2.15% ash, and 69.435 -75.625% carbohydrates, while the caloric values of oat flours were 412.5 and 414.01 kcal /100 g for both red and common oat. On the other hand, the results in the same Table 2 appeared that unripe banana flour(UBF) contained moisture (6.79%), crude protein (4.80%), crude fat (5.16%), ash (2.95%0, crude fiber (13.03%), total carbohydrates (84.93%) and caloric value (363.56 kcal/100g).…”
Section: Gross Chemical Composition and Caloric Value Of Oat And Unri...mentioning
confidence: 99%